SOSIALISASI PENERAPAN TERAPI KOMBINASI REBUSAN DAUN SELEDRI DAN MADU DALAM MENURUNKAN TEKANAN DARAH PADA LANSIA - Suci Hardianti; Herwed Nelson D; Nirwana, Nirwana (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Hypertension is a degenerative disease often experienced by the elderly and is a major risk factor for heart disease and stroke. Non-pharmacological treatment efforts with herbal therapy are starting to be widely developed, one of which uses celery leaves (Apium graveolens L.) which have a natural diuretic effect, and honey which contains high antioxidants that can help lower blood pressure. The combination of the two is believed to provide a synergistic effect in lowering blood pressure in the elderly. This community service activity aims to improve the knowledge and skills of the community and cadres at the UPTD PKM Bojong, Purwakarta Regency in carrying out non-pharmacological therapy, applying a combination therapy of celery leaf decoction and honey in lowering blood pressure in the elderly in the work area of ​​​​the UPTD PKM Bojong, Purwakarta Regency. The method of implementation of the activity uses a lecture approach, demonstration, and simulation. The activity participants were 40 people consisting of the general public and health cadres. Evaluation was carried out using a pre-test and post-test to assess the increase in knowledge, as well as observation of skills during the simulation practice. The combination therapy of celery leaf decoction and honey is effective in lowering blood pressure in the elderly with hypertension. This therapy can be used as a non-pharmacological alternative that is easy, safe, and economical to control blood pressure in the elderly